2022
DOI: 10.1136/bmjopen-2022-063316
|View full text |Cite
|
Sign up to set email alerts
|

Online information in Spanish on probiotics, yoghurt, kefir, kombucha, fibre and prebiotics: an analysis of the quality of information and the certainty of the evidence supporting health claims

Abstract: ObjectiveTo examine the certainty of the evidence supporting health claims about probiotics, yoghurt, kefir, kombucha, fibre and prebiotics, and to assess the quality of online information in Spanish.DesignContent analysis.MethodsWe compiled a data set of 114 web pages by searching six popular search phrases in Spanish relating to probiotics, yoghurt, kefir, kombucha, fibre and prebiotics on Google.es and coded them for typology and health claims. We examined the certainty of the evidence for health claims fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 90 publications
(175 reference statements)
0
4
0
Order By: Relevance
“…Given that several information quality assessment tools evaluate references of information (12)(13)(14) , referencing is considered a minimal requirement for reliable information but does not fully guarantee the reliability of the information. In previous studies, diet health claims extracted from a book, newspapers and websites were evaluated based on the scientific evidence that supported the claims (41)(42)(43)(44) . Although our present study did not evaluate the accuracy of the claims in the books, mainly because each book contained a large number of claims, this is an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that several information quality assessment tools evaluate references of information (12)(13)(14) , referencing is considered a minimal requirement for reliable information but does not fully guarantee the reliability of the information. In previous studies, diet health claims extracted from a book, newspapers and websites were evaluated based on the scientific evidence that supported the claims (41)(42)(43)(44) . Although our present study did not evaluate the accuracy of the claims in the books, mainly because each book contained a large number of claims, this is an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also showed that some nutrition claims in newspapers were based on evidence with an insufficient grade (43) . Regarding other languages, most online health claims in Spanish to improve health through gut microbiome were supported by evidence described as low or very low certainty of the effect in systematic reviews (44) . Taking these previous and our present results together, books and online information about diet and health may frequently not cite sufficient references and may be supported by evidence with insufficient grade in English as well as in other languages.…”
Section: Discussionmentioning
confidence: 99%
“…Given the widespread interest among nutrition and PA communicators in using social media to reach large numbers of people, it is important to synthesize the available research evidence on the effectiveness of such efforts. Research that supports the dissemination of evidence‐based messages on social media may be especially critical to combat the proliferation of inaccurate or misleading information on those channels 13–16 . Prior reviews have explored the effects of multicomponent diet‐ and PA‐related interventions without evaluating the independent effects of social media components or have examined the effects of intensively moderated, limited‐reach social media programs (e.g., private online discussion boards or social media groups) 4,17–20 .…”
Section: Introductionmentioning
confidence: 99%
“…Research that supports the dissemination of evidence-based messages on social media may be especially critical to combat the proliferation of inaccurate or misleading information on those channels. [13][14][15][16] Prior reviews have explored the effects of multicomponent diet-and PA-related interventions without evaluating the independent effects of social media components or have examined the effects of intensively moderated, limited-reach social media programs (e.g., private online discussion boards or social media groups). 4,[17][18][19][20] However, no prior reviews have focused specifically on studies testing the independent effects of social media campaigns that promote healthy eating, PA, and healthy weight and do not include intensive moderation that might limit campaign reach.…”
mentioning
confidence: 99%